The clinical predictors of aetiology and complications among 173 patients presenting to the Emergency Department with oesophageal food bolus impaction from 2004–2014. Issue 1 (12th May 2015) - Sengupta, N.; Tapper, E. B.; Corban, C.; Sommers, T.; Leffler, D. A.; Lembo, A. J.
Summary Background Oesophageal food bolus impaction (OFBI) is a common gastrointestinal emergency. Aim To describe contemporary aetiologies of OFBI, and variables that may predict eosinophilic esophagitis (EoE) related OFBI as well as complications. Methods Patients presenting to the Emergency Department between 2004 and 2014 with OFBI who underwent oesophagogastroduodenoscopy (EGD) were included. Clinical and endoscopic variables, as well as complications, were recorded. Aetiology of OFBI was determined by reviewing endoscopy reports. A diagnosis of EoE was confirmed via pathology (>15 eosinophils/high‐powered field) at the index or follow‐up EGD. Logistic regression was used to report associations of variables and complications. Results Of the 173 patients with OFBI, 139 (80%) had an aetiology recognised, the most frequent being EoE (27%, n = 47), Schatzki's ring (20%, n = 34) and oesophageal stricture (13%, n = 22). Six patients (3%) had oesophageal cancer. Patients with EoE‐related OFBI tended to be younger (42 vs. 69 years, P < 0.001), male (81% vs. 52%, P = 0.001), have a prior history of OFBI (45% vs. 18%, P = 0.001), and present during spring or summer (62% vs. 44%, P = 0.04). Eighteen patients (10%) had a complication associated with OFBI, with 3 (2%) perforations. On multivariate regression, patients with EoE‐related OFBI were not more likely to have a complication (OR 1.07, P = 0.92), although hypoxia at presentation (OR 59.7, P = 0.006) was associated with complications. Conclusions Eosinophilic esophagitis accounts for over a quarter of patients with oesophageal food bolus impaction. Overall complication rate was 10%, with a 2% perforation rate. Clinical characteristics of patients with eosinophilic esophagitis differ from other patients with oesophageal food bolus impaction.